The phosphorus as lecithin, protein and inorganic compounds in the yolk of egg - Hole, Gertrude Elma (My University, 1906)
Introduction: In making the chemical analysis of eggs we find that the white is composed of water and protein, or almost pure albumen, and a minute quantity of inorganic salts; but the yolk is quite different, it having about 50% of water and the remainder solid matter—which is protein, ether extract and inorganic compounds. In analyzing a portion of this solid yolk we find that there exists in it a considerable portion of phosphorus. The question then occurs, “How much of this phosphorus exists as organic and in what form does it exist”? There is a substance in the yolk of egg known as lecithin which as yet is not thoroughly understood but whose importance can be judged form the summary which W. Maxwell gives in his valuable work on the subject of egg-analysis. “Lecithins are a source of the phosphorus required by the animal organism in the formation of bone. These bodies are also the medium by which the phosphorus present in vegetable organisms is received by the animal organism.” His investigations have shown finally “That the lecithins exercise the function of receiving phosphorus from minerals and bestowing it in the processes of the animal organism in the formation of bone. These bodies are thus the medium through which the element performs its movements, through the vegetable and into the animal kingdom.”
Citation: Hole, Gertrude Elma. The phosphorus as lecithin, protein and inorganic compounds in the yolk of egg. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Chemistry; Egg Yolk; Theses; Manuscripts (documents)